Creating Project-Activity Educational Environment for Innovative Training of Future Engineers - Nikolai I. Naumkin; Dmitry E. Glushko; Vladimir F. Kupryashkin; Zulfiya Kh. Abushaeva (National Research Mordova State University, 2024)
Introduction. Training students for innovative engineering activity is one of the priority tasks of an engineering university. However, so far all existing approaches to its solution involve changes in the curricula of degree programmes. The aim of the research is to substantiate and develop a methodological system of training future engineers in innovative engineering activity in the educational environment. Materials and Methods. The methodology of innovative engineering education, environmental, project, convergent and other approaches was used. A quantitative assessment of the level of development of innovative competencies was carried out during a comparative training experiment based on the average indicator of time series. The Pearson test was used to assess the statistical significance of the data. Results. The possibility of preparing future engineers for innovative engineering activities during a comprehensive course projecting in general engineering disciplines without departure from the curriculum is substantiated. To create conditions for such training, a project-based and activity-based educational environment has been proposed, pooling into one system all the resources available at the university and ensuring their interaction on the basis of a convergent approach associated with the approximation and interpenetration of scientific, pedagogical and information technology knowledge. A system for teaching innovative engineering activities in this environment has been developed, including conceptual-target, content, procedural-technological and reflective components, implemented within the framework of a business game. Discussion and Conclusion. The conclusions made by authors contribute to the development of the environment approach to learning in terms of designing new educational environments, theory and methodology of teaching technical disciplines, as well as project-based learning - in terms of their focus on innovative training of students.